The Urgency of Multicultural Islamic Education, Democracy And Human Rights In Indonesia - Abduloh, Agus Yosep; Ruswandi, Uus; Erihadiana, Mohamad; Mutmainah, Naeli; Ahyani, Hisam (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2022)
On the one hand, in the 4.0 era, contemporary Islamic education cannot avoid the phenomenon of interrelationships between human beings in the increasingly intensive and pluralistic systems of technology, information and communication. This era demands the practice of Islamic education with a multicultural perspective, democracy and human rights. On the other hand, there is an unpreparedness in the practice of Islamic education to face these challenges, such as teaching staff who do not understand multicultural education, learning materials and resources that are biased by social class, gender, ethnicity, religion, and urban areas. The purpose of this study is to determine the urgency of multicultural Islamic education, democracy and human rights in Indonesia, and to demonstrate the complexity of the challenges. The results show that multicultural Islamic education can be implemented by teachers, leaders, school members and campus communities in the 4.0 era if these stakeholders have a multicultural attitude, which is characterized by the ability to manage challenges of primordialism, ethnicity, religion and social class. The Islamic concept of Rahmatan Lil 'Alamin can be a solution and method of contemporary Islamic education practice that is in accordance with the learning material and the development of the student's soul.